The Nanomechanical Performance and Water Uptake of a Flowable Short Fiber Composite: The Influence of Bulk and Layering Restorative Techniques - Tarjányi, Tamás; Jakab, András Gábor; Sámi, Márton; Bali, Krisztián; Rárosi, Ferenc; Jarábik, Maja Laura; Braunitzer, Gábor; Palkovics, Dániel; Lassila, Lippo; Lempel, Edina; Fráter, Márk; Garoushi, Sufyan (MDPI AG, 2025)
This study aimed to evaluate the nanomechanical surface properties and water uptake of a flowable short-fiber-reinforced composite (SFRC) using various restorative techniques in order to assess its potential as a standalone restorative material. Nanoindentation and compressive creep testing were employed to characterize material performance. Three resin composites were examined: a flowable SFRC (everX Flow), a bulk-fill particulate filler composite (PFC), and a conventional PFC. Five experimental groups were established based on the restorative technique: layered PFC, layered SFRC, bulk SFRC, bulk PFC, and a bi-structure combining SFRC and PFC. Ninety standardized specimens (n = 18/group) were fabricated. Static and creep nanoindentation tests were conducted to assess surface properties, and water uptake was measured over a 30-day period. Data were analyzed using one-way ANOVA and Bonferroni post hoc tests. Nanoindentation revealed significant differences in hardness, with bulk PFC exhibiting the lowest values (p < 0.001). Creep testing indicated changes in modulus and viscosity following water storage. Notably, bulk SFRC showed the lowest water absorption (p < 0.001). Overall, bulk-applied SFRC demonstrated favorable nanomechanical properties and reduced water uptake, demonstrating its suitability as a standalone restorative material. Further clinical investigations are recommended to validate its long-term performance.